Impact of agricultural planning policy in Economical Return improve of non-irrigated crops farmers in the first Zone of Qamishli District (Al -Hassakae Governorate) (Damascus University Journal of agriculture sciences, 2021)
The research aims to determine the impact of agricultural policy planning in improving the economic returns to farmers in non-irrigated crop area in district study. It was implemented on the basis of preliminary data by form prepared for this purpose, and secondary dealt with data plans agricultural seasons of 2007/2008 and even 2011/2012 in the area of district study, and its implemented, was selected sample of 45 villages a sample stratified random from the villages of district study, The sample size was 201 farmers. Method was applied linear programming model, to maximize the profit resulting from the production of non-irrigated crops in the area of ​​ district study, based on the net profit achieved in the unit area of ​​one (ha). The results of the analysis showed that the optimal solution of the model at its adoption suggests production plan permits the cultivation of all crops studied, according to the suitable percentage, and achieve the highest net profit of 7013.9 billion Sl, where this increases profit by 1654.6 billion Sl, compared to implemented current, an increase of increase of 30.9 %, and about 1383.5 billion Sl, compared to the Plan, an increase of 24.6%.
Keywords: Agricultural Planning, Non-irrigated crops, Economic Revenue